Implementasi Strategi Komunikasi Adaptasi dan Mitigasi Perubahan Iklim Berbasis Masyarakat melalui Program Kampung Iklim di Kabupaten Magelang - Karima, Fadilatul (Jurnal KIRANA, 2022)
Drought and landslide disasters in Magelang Regency have moved people in Margoyoso Village and Sambak Village to carry out adaptation and mitigation activities as responses to the vulnerability experienced. The Government of Magelang Regency, strengthening climate grassroots movements through the Kampung Iklim Program by encouraging the involvement of stakeholders at the cross-level to support ProKlim activities. The research was conducted on October 13, 2021, until January 4, 2022. This research uses a qualitative method, to reveal and understand the implementation of ProKlim's communication strategy based on the information, views, and experiences of key informants. The results show that the implementation of the ProKlim communication strategy in Magelang Regency is carried out through actions of effective communication that synergize elements of advocacy, social mobilization, and participation. Strengthening the local people community, has encouraged community participation and behavior change at the individual level.